Treatment of Gastroenteritis in COVID-19 children - Chandrika Murugaiah; Constance Liew Sat Lin; Hassanain Al-Talib; Mehru Nisha; Tunung Robin; Tuan Zainazor Tuan Chilek; Atif Amin Baig; Rhanye Mac Guad; May Zaw Soe; ABM Tofazzal Hossain; Falah Abbas Mohamad Salih; Mustafa al Shagga (2020)
SARS-CoV-2 is highly contagious and has resulted in a rapid pandemic of COVID-19 that posing a threat to public health. They are causing a severe acute respiratory syndrome and known to infect the neurological, enteric, and hepatic systems. The aim of this document is to provide recommendations for a systematic approach for the gastroenteritis treatment in COVID-19 children where most important treatment options where discussed.